FILSAFAT MORAL DALAM SERAT CENTHINI MELALUI TOKOH SEH AMONGRAGA SUMBANGANNYA BAGI PENDIDIKAN KARAKTER - , SUTRISNA WIBAWA, Prof. Dr. Joko Siswanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is entitled Moral Philosophy in Serat Centhini through Seh Amongraga Character, Its Contributions to Moral Education. Seh Amongraga, being the main character in Serat Centhini, is described as a superior human, saint, or guardian. As a guardian, the teachings of Seh Amongraga contain high moral values, as a result the public needs to be acquainted with it. There fore related to moral values and its contribution to character education, the assessment in this study uses the standpoint of moral philosophy. This study aims to (1) explore and formulate the foundation of Serat Centhiniâs philosophy (2) conduct a critical analysis of the moral teachings in Serat Centhini through Seh Amongraga figure, and (3) find its contribution to the moral teachings found in Serat Centhini through Seh Amongraga figure for character education. This study uses qualitative methods. The primary source is the text of Serat Centhini, while secondary sources are literature and research results which discussed Serat Centhini. Research process is to follow the steps of data collection, data reduction, data classification, data display, and conclusion. The analysis of the data is using the two basic methods which are the methods of hermeneutics and heuristics. This study first result is Javanese philosophy is a philosophy which emphasizes the importance of the perfection of life (ngudi kasampurnan) and the philosophy of the origin and direction of existence (sangkan paraning dumadi). The perfection of life shown by the human mind in contemplating himself is to find integrity in relationship with God. Philosophy of the origin and its direction is indicated by the act of the human life and united in moves to wards perfection. The philosophy of Serat Centhini is formed based on Javanese philosophy, because in the Serat Centhini, it contains teachings and philosophy the perfection of life that is the origin and direction, which are reflected in the foundation of ontology, epistimology, and axiology. Secondly, the moral values of Seh Amongraga in Serat Centhini, which consists of the rights and obligations, justice, responsibility, conscience, honesty, moral courage, humility, and loyalty, are good guides for human behavior. The moral values are as a reference guide for a person or group of people in regulating their conduct and as a benchmark for determining whether the attitude and action of human being good or not. Thirdly, the moral philosophy of Seh Amongraga in Serat Centhini gives a real contribution in enriching the character-forming values of YSUâs models of character education and that of Ministry of Education and Culture.